Giant Borderline Mucinous Cystadenoma in a Multiparous Woman: A Case Report - Singh, Karnel (Miracle Journal of Public Health, 2025)
Cystic lesions with loculi lined with mucin-producing epithelium are mucinous ovarian tumors. Approximately 10% of these are borderline tumors. These cysts are commonly found in 30-50 year olds. Ovarian cysts exceeding 10 cm in diameter are called giant ovarian tumors. This study aims to present a case of Giant Borderline Mucinous Cystadenoma in a multiparous woman. Report a case of a 38-year-old woman P3A0 presenting with an enlarged abdomen for approximately 1 year and tightness 1-month SMRS, which was later diagnosed as Giant Borderline Mucinous Cystadenoma. Mucinous cystadenoma has the potential to grow into a large mass and rarely goes undiagnosed until it becomes a giant ovarian cyst (>10 cm). Total Abdominal Hysterectomy, Salpingo Oophorectomy Sinistra, right salpingectomy, right partial oophorectomy, ascitic fluid aspiration, left pelvic lymphadenectomy, and omentectomy were performed. Transabdominal Ultrasound showed a mixechoic image of the adnexa with a size of 23.2 cm x 15.9cm x 27 cm with a volume of 5265 cc. PA result showed borderline cystadenoma mucinous. The therapeutic strategy was guided by FIGO classification, age, and the patient's desire to have children. Early recognition and management are crucial to prevent disease progression and reaching giant tumor size.